Upaya Orang Tua Mendampingi Anak- Anak Dalam Hal Berdoa Di Stasi ST. Yosef Ampari Bura Dalam - Sigit Wibowo; Silvester Adinuhgra; Agnes Angi Dian Winei (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
This study depicts the efforts made by parents and the experiences of children in the process of teaching prayers at St. Joseph's Ampari Bura Dalam Chapel. Teaching prayers to children yields positive effects on their spiritual development. The primary focus of this study is the challenges faced by children in cultivating prayer skills. Parents play a pivotal role in ensuring the spiritual growth of children by guiding, educating, and encouraging them to pray, with the aim of establishing prayer habits and self-confidence. A qualitative approach and descriptive method are employed in this research. Data is collected through interviews with four parents and four children. The gathered information is analyzed using the